On Flat Objects of Finitely Accessible Categories - Septimiu Crivei (The Scientific World Journal)
Flat objects of a finitely accessible additive category are described in terms of some objects of the associated functor category of , called strongly flat functors. We study closure properties of the class of strongly flat functors, and we use them to deduce the known result that every object of a finitely accessible abelian category has a flat cover.